Prevalence and Associated Factors of Overweight and Obesity among Primary School Children Aged 7–17 Years in Urban Mbarara, Uganda - Benedict Twinomugisha; Abdon Marius Birungi (Advances in Public Health)
Globally, overweight and obesity among children have been acknowledged as a growing public health concern. In sub-Saharan Africa, the prevalence of overweight and obesity is high. In Uganda, there is a significant burden of overweight and obesity. This study was conducted to determine the prevalence and associated factors that influence overweight and obesity among primary school children in Southwestern Uganda. A cross-sectional study utilized a self-administered questionnaire and anthropometric tools to collect data. A three-stage sampling procedure was used to select four schools that participated in this study. A total of 422 children participated in our study. Participant’s weight and height were measured using SECA Scale, Model 885, and a wall-mounted stadiometer, respectively. Data were analyzed using STATA v11.0. The prevalence of overweight/obesity was descriptively analyzed. Associated factors were determined using bivariate and multivariate analysis. Findings revealed that 54.3% of participants were walking to school compared to 45.7% that were cycling/bicycling and 76.3% playing and doing household chores as opposed to 23.7% that spent their leisure time through reading and watching TV, 74.2% took more than two meals per day, and 79.4% often took vegetables and fruits compared to 20.6% that took them most of the time. The study found an overall prevalence of 20% for overweight/obesity. There was a statistical association between overweight/obesity and ownership of residence (O.R.: 0.4, 95% C.I.: 0.2–0.8), modes of transport (O.R.: 8.2, 95% C.I.: 3.4–20.0), leisure time activities (O.R.: 0.4, 95% C.I.: 0.2–0.7), frequency of consuming vegetables and fruits (O.R.: 2.8, 95% C.I.: 1.4–5.5), and the type of school attended (O.R.: 0.2, 95% C.I.: 0.1–0.4). However, only the mode of transport (A.O.R.: 5.0, 95% C.I.: 1.9–13.0) was independently associated with overweight/obesity on multivariate logistic regression analysis. Girls who participated in our study were more overweight than boys. Overweight/obesity existed more in private schools than public schools. Modes of transport were only found to be strongly associated with overweight/obesity. There is a need to establish evidence-based strategies to inform policy on prevention of childhood overweight/obesity.